1989
DOI: 10.1103/physrevb.39.1747
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic superexchange and spin-resonance linewidth in diluted magnetic semiconductors

Abstract: The Dzyaloshinski-Moriya (DM) anisotropic superexchange constant and the resulting electronparamagnetic-resonance (EPR) linewidth in Mn-based II-VI-compound diluted magnetic semiconductors {DMS) such as Cd 1 Mn Te are calculated quantitatively.An Anderson Hamiltonian, developed in a previous study of isotropic superexchange, describing correlated Mn 3d states hybridized with semiconducting sand p-derived levels, is generalized to include the anion spin-orbit coupling responsible for anisotropic superexchange. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
1

Year Published

1995
1995
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 88 publications
5
59
1
Order By: Relevance
“…The same analysis also gave an estimate for the DM constant D1 . All these results (magnitude and sign of ΔJ1, and value of D1) agree with theory [8,18].…”
Section: Inequivalent Nnssupporting
confidence: 79%
See 1 more Smart Citation
“…The same analysis also gave an estimate for the DM constant D1 . All these results (magnitude and sign of ΔJ1, and value of D1) agree with theory [8,18].…”
Section: Inequivalent Nnssupporting
confidence: 79%
“…Among the other interactions between the magnetic ions the most important is the Dzyaloshinski-Moriya (DM) interaction, of the form The largest Dij is expected to be D1. Its magnitude for Mn-based DMS was calculated by Larson and Ehrenreich [8]. They found that it increases with the atomic number of the anion.…”
Section: Magnetic Ions and Their Interactionsmentioning
confidence: 99%
“…The former repreSent the contribution from all singly occupied ionic orbitals, whereas the latter the contribution from the doubly occupied eg orbitals. After putting S = 5/2 and noting that in Mn 2 + ions all 5d-orbitals are singly occupied, one gets from (3) the results compatible with those of Larson and Ehrenreich [6].…”
supporting
confidence: 75%
“…Using a perturbative k-space approach Larson et al [5] have shown that the superexchange, reSulting from sp-d hybridization, is by far the dominant spin-spin interaction mechanism in AIIBVI DMS. In papers [5] and [6] the authors, considering the case of the S-like Mn2 ± magnetic ion, have used the simplest Anderson model to approximate the ionic energy spectrum. Furthermore, in the calculations of isotropic exchange [5] the ionic orbital dependence of the hybridization Hamiltonian was neglected.…”
mentioning
confidence: 99%
See 1 more Smart Citation